1999
DOI: 10.1117/12.358430
|View full text |Cite
|
Sign up to set email alerts
|

<title>Trace element analysis in water by LIBS technique</title>

Abstract: The results obtained for contaminant detection in water, with the recently implemented LIBS technique, are presented. A Q-Switched Nd-YAG laser (1,06 .tm) was used, focusing its output on the sample. Two experimental set-ups are used; in the first spark was generated in the bulk of the liquid, while in the second it was generated at its surface. We found the latter useful because it gave more information on several ionic elements present in the aqueous solution. The linearity of the system and its limits of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Cremers et al [17] note that in the case of a plasma induced in a solution of CaCl 2 the emission of Ca is observed after the emission of Ca + . The same behavior is observed in the case of MgCl 2 [18]. The observations of these authors and others mentioned in the study presented elsewhere [1], lead to conclude that the electron ion recombination can be at the origin of the formation of the excited species.…”
Section: Introductionsupporting
confidence: 77%
“…Cremers et al [17] note that in the case of a plasma induced in a solution of CaCl 2 the emission of Ca is observed after the emission of Ca + . The same behavior is observed in the case of MgCl 2 [18]. The observations of these authors and others mentioned in the study presented elsewhere [1], lead to conclude that the electron ion recombination can be at the origin of the formation of the excited species.…”
Section: Introductionsupporting
confidence: 77%
“…For the elimination of toxic organic molecules or the detection of hazardous metallic contaminants of spoiled water, several plasma processes are involved such as radiofrequency plasmas [1], dc torches [2][3][4], transferred arcs [5][6][7][8] or pulsed discharges [9]. There are also many works dealing with trace element analysis or contaminant detection in aqueous solutions using laser induced breakdown spectroscopy (LIBS) [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of plasma induced on the solution of MgCl 2 , the emission of Mg + is observed before the emission of Mg [15,19] as the emission of Ca + and Ca in the case of CaCl 2 [5,14]. In our previous study, we have shown that this temporal shift in the apparition of ion and atomic emission can be attributed to recombination of electron created during the interaction of laser pulse with solution and ions ejected from the solution.…”
Section: Kinetics Of the Laser Induced Plasmamentioning
confidence: 87%